THE VICTIM OF THE CRIME OF HUMAN TRAFFICKING FROM A HUMAN PERSPECTIVE - MARIO ALBERTO NUÑEZ LAURA (2020)
The uniform criterion that is held, by the persons involved in the legal field, society as a whole and the organizations committed to supporting the victims of the different acts of violence or against the law existing in our country, within them, the victim of the crime of human trafficking is that the consideration, treatment or concern that is had by the victim, as a human being is deficient, this in the framework of the welfare responsibility that has the State and the society as a whole, with respect to that person who by bad luck or wrong decisions has fallen into the clutches of the organizations of traffickers in persons, The victim, within our national reality, is seen only as a file number at the judicial level or as a folder number within the fiscal sphere, leaving aside the human aspect, the dignity of that person is unknown or does not take into account the needs, requirements, social, family or economic situation of that victim, allowing the ignorance of the condition in which this human being is aggrieved, leading to a lack of empathy in the servers and people, which in one way or another could help, assist or protect that victim.